G2 domain walls in M theory - House, T; Lukas, A (2005)
M theory is considered in its low-energy limit on a G2 manifold with nonvanishing flux. Using the Killing spinor equations for linear flux, an explicit set of first-order bosonic equations for supersymmetric solutions is found. These solutions describe a warped product of a domain wall in four-dimensional space-time and a deformed G2 manifold. It is shown how these domain walls arise from the perspective of the associated four-dimensional N = 1 effective supergravity theories. We also discuss the inclusion of membrane and M5-brane sources. © 2005 The American Physical Society.